Fluctuation of associated microbial with building reef corals \(Acropora\) sp. from Hang Rai, Ninh Thuan - Pham, Thi Mien; Nguyen, Kim Hanh; Phan, Minh Thu; Nguyen, Minh Hieu; Vo, Hai Thi; Nguyen Trinh, Duc Hieu; Hoang, Trung Du; Nguyen , Huu Huan (Vietnam Journal of Marine Science and Technology, 2022)
El Niño and the prolonged warm sea surface temperature significantly impacted coral reefs and caused coral bleaching in some parts of the world. This study evaluated the density of symbiotic algae and bacteria associated with the three coral species, namely Acropora hyacinthus, Acropora muricata, and Acropora robusta, collected in Hang Rai, Ninh Thuan in May, June, August 2016, and June 2017. The number of zooxanthellae with each coral species was statistically significant and correlated with several environmental factors, suggesting that symbiotic algae could play a key role in coral health. The number of associated microbial with the three coral species was significantly different; they tended to depend on sampling time rather than coral species-specific. At the time of ENSO (2016), the difference in the total associated bacteria with all three coral species was statistically significant. While the total number of related bacteria with all three species of coral collected in 2017 did not differ from the total of bacteria in ambient water. In conclusion, symbiotic algae tend to be species-specific, whereas bacteria fluctuate significantly over sampling time. Studying the molecular issues of microalgae, the presence, the role of some groups of bacteria involved in the N, C, P, and S cycles, and the influence of environmental parameters should also be encouraged to understand the relationship of coral holobiont better.